Kinematic analysis of take-off performance in elite swimmers: New OSB11 versus traditional starting block - Biel, K.; Fischer, S.; Kibele, A. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: Recently, a new starting block (OSB 11 from Omega Swiss Timing, Ltd.) was introduced to FINA international swimming competitions. While the distributor of this new block advertises its product to result in shorter race times studies to examine the kinematic changes associated with the new construction are scarce. A study was conducted to compare the kinematic take-off profiles of german elite swimmers from the new starting block (surface area 74x50 cm, 9° surface angle to the ground) and from the traditional starting block (surface area 50x50 cm, 5° surface angle to the ground). METHOD: Seven male swimmers (3 grab starters and 4 track starters) participated in the study. Their take-off performances were videotaped and later on examined for selected kinematic parameters. The last ten frames during the block phase and the first five frames in the flight phase were analyzed (take-off angle and take-off velocity related to the centre of mass trajectory). A second video camera was used to measure the starting performance by the time elapsed between the starting signal and the passage of the head at 7,5 m. Each subject performed three track starts on the new OSB 11, three track starts on the traditional starting block, and three grab starts on the new OSB 11. The best two trials for each condition were used for the statistical analysis. RESULTS: For the track starts, starting performance was significantly reduced by 0,2 s in the new OSB 11. In addition, a shorter block time and a higher horizontal takeoff velocity were found for the new block. For the comparison between the two starting techniques on the new block, track starters showed significantly shorter starting times and block times as well as a significantly higher horizontal take-off velocity. While significantly a better starting performance was found for the new OSB 11, our results also indicate that a modification of the dive-in behaviour may be necessary to fully utilize the possibilities of the new starting block.